Makna Persahabatan Dalam Lagu Kana Nishino “Best Friend” - Mugiyanti Mugiyanti; Candra Rizki Permana (Universitas Pakuan, 2021)
ABSTRACT: A song it is said to become popular if is known and loved almost throughout the world. Each song has different meanings and intentions, according to the purpose of the author. Kana Nishino is popular Japanese musician who create many hit songs in Japan. One of her songs which is she created “Best Friend